Forecasting the Impact of Knowledge of International Humanitarian Law Acquired by Ukrainian Medical Students on Their Practical Activities and the Formation of Humanity in Society - Soroka, Oksana; Voloshynovych, Volodymyr; Kotsyubynska, Yulia (Acta medica Lituanica, 2026)
Purpose: International humanitarian law (IHL) and the principle of medical neutrality are vital for safeguarding human life and dignity during armed conflicts. This study aimed to evaluate the current state of IHL education in Ukrainian medical institutions and forecast its impact on future healthcare professionals’ professional practice and humanistic orientation.Methods: A mixed-methods design was applied, including content analysis of curricula from 17 higher education institutions across different ministries and an online sociological survey of 174 respondents, primarily medical students and healthcare professionals. Quantitative data were analyzed by using frequency distributions and Spearman correlation, while qualitative analysis explored the respondents’ ethical reasoning in conflict-related scenarios.Results: Only one-third of Ukrainian medical universities included dedicated IHL courses, primarily as electives. Self-reported awareness of IHL was low to moderate, with 23% rating their knowledge as good and 26% as poor. Despite this, 81.4% of medical students agreed with impartial medical assistance to all victims, regardless of affiliation. A weak but positive correlation (ρ=0.15) was found between IHL knowledge and humanitarian attitudes. Female students demonstrated stronger humanitarian orientations compared to males.Conclusion: IHL education in Ukraine remains fragmented and insufficient, yet students display a high ethical potential aligned with humanitarian principles. Structured, value-oriented IHL curricula, including practical training and case-based learning, are needed to strengthen medical neutrality, enhance ethical decision-making, and foster the formation of humanistic values in Ukrainian society.
Keywords: armed conflict; medical education; humanism; international humanitarian law; medical students; Ukraine